Berufliche Bildung in Japan : gesellschaftliche Wertschätzung und Unternehmenspartizipation - Pilz, Matthias [Verfasser]; Alexander, Peter-Jörg [Verfasser] (My University, 2016)
"Vocational education in Japan is unique. One the one hand the paper analyses the attractiveness and reputation of vocational education in Japan. The results are showing a less strict device between general/higher and vocational education. Much more important is the transition into a regular lifetime employment position in a big company with high reputation. On the other hand the paper discusses the phenomena of the wide ranging company involvement into internal vocational training. The reason for this in internal terms unique situation can be found in an internal logic of the company's behavior in relation to the internal and external labour market situation and also by including cultural expectations by the general public and the individual employee." (Authors' abstract, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 3.2 Unternehmen und Behörden; I 2.3.4 Asien; Berufsbildung; Betriebliche Berufsausbildung; Attraktivität; Unternehmen; Betriebszugehörigkeit; Japan